Teacher Education Students’ Perceptions and Motivation in taking a Pre-service Teacher Professional Program - Hapsari, Nofita; Arief, Sandy; Khaerudin, Teguh (Dinamika Pendidikan, 2020)
This study aims to examine students’ perception of PPG-SM3T on motivation to participate the teacher professional education program. PPG-SM3T is a professional development program for pre-service teacher in Indonesia. Data for this study were collected from 186 students of economics education using a survey questionnaire. The findings showed that students’ perception of PPG-SM3T positively associated with motivation to participate the program. In addition, the study found that a majority of participants realized that teacher professional development program is significantly important to prepare them to be professional teachers. They also raised concerns, challenges, and the need to participate PPG-SM3T. Findings also suggested that providing information and active socialization on PPG-SM3T may motivate them to participate in the program.